Effect of a retinoid X receptor partial agonist on airway inflammation and hyperresponsiveness in a murine model of asthma. Issue 1 (December 2017) - Fujii, Utako; Miyahara, Nobuaki; Taniguchi, Akihiko; Oda, Naohiro; Morichika, Daisuke; Murakami, Etsuko; Nakayama, Hikari; Waseda, Koichi; Kataoka, Mikio; Kakuta, Hiroki; Tanimoto, Mitsune; Kanehiro, Arihiko
Abstract Background Retinoid X receptors (RXRs) are members of the nuclear receptor (NR) superfamily that mediate signaling by 9-cis retinoic acid, a vitamin A (retinol) derivative. RXRs play key roles not only as homodimers but also as heterodimeric partners—e.g., retinoic acid receptors (RARs), vitamin D receptors (VDRs), liver X receptors (LXRs), and peroxisome proliferator-activated receptors (PPARs). The NR family was recently associated with allergic diseases, but the role of RXRs in allergen-induced airway responses is not well defined. The goal of this study is to elucidate the role of RXRs in asthma pathogenesis and the potency of RXR partial agonist in the treatment of allergic airway inflammation and airway hyperresponsiveness using a murine model of asthma. Methods We investigated the effect of a novel RXR partial agonist (NEt-4IB) on the development of allergic airway inflammation and airway hyperresponsiveness (AHR) in a murine model of asthma. Balb/c mice were sensitized (days 0 and 14) and challenged (days 28–30) with ovalbumin (OVA), and airway inflammation and airway responses were monitored 48 h after the last OVA challenge. NEt-4IB was administered orally on days 25 to 32. Results Oral administration of NEt-4IB significantly suppressed AHR and inflammatory cell accumulation in the airways and attenuated the levels of TNF-α in the lung and IL-5, IL-13 and NO levels in bronchoalveolar lavage (BAL) fluid and the number of periodic acid Schiff (PAS)-positive goblet cells in lung tissue. Treatment with NEt-4IB also significantly suppressed NF-κB expression. Conclusion These data suggest that RXRs may be of crucial importance in the mechanism of allergic asthma and that the novel RXR partial agonist NEt-4IB may be a promising candidate for the treatment of allergic airway inflammation and airway hyperresponsiveness in a model of allergic asthma.